Ecomorphological analysis of bovid mandibles from Laetoli Tanzania using 3D geometric morphometrics: Implications for hominin paleoenvironmental reconstruction. Issue 114 (January 2018) - Forrest, Frances L.; Plummer, Thomas W.; Raaum, Ryan L.
Abstract: The current study describes a new method of mandibular ecological morphology (ecomorphology). Three-dimensional geometric morphometrics (3D GM) was used to quantify mandibular shape variation between extant bovids with different feeding preferences. Landmark data were subjected to generalized Procrustes analysis (GPA), principal components analysis (PCA), and discriminant function analysis (DFA). The PCA resulted in a continuum from grazers to browsers along PC1 and DFA classified 88% or more of the modern specimens to the correct feeding category. The protocol was reduced to a subset of landmarks on the mandibular corpus in order to make it applicable to incomplete fossils. The reduced landmark set resulted in greater overlap between feeding categories but maintained the same continuum as the complete landmark model. The DFA resubstitution and jackknife analyses resulted in classification success rates of 85% and 80%, respectively. The reduced landmark model was applied to fossil mandibles from the Upper Laetolil Beds (∼4.3–3.5 Ma) and Upper Ndolanya Beds (∼2.7–2.6 Ma) at Laetoli, Tanzania in order to assess antelope diet, and indirectly evaluate paleo-vegetation structure. The majority of the fossils were classified by the DFA as browsers or mixed feeders preferring browse. Our results indicate a continuous presence of wooded habitats and are congruent with recent environmental studies at Laetoli indicating a mosaic woodland-bushland-grassland savanna ecosystem.